PENGEMBANGAN USAHA HORTIKULTURA PETANI KECIL - ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Bali still has big potency to develop of fruits horticulture through the effort intensification. This matter is supported by: (i) availability of dry land of 126.487 ha can be cultivated intensively, availability of rice field of 87.765 ha can be cultivated for horticulture rotating, high land fertility and specific, agroclimate suited for development various horticulture crop type, (ii) Bali has potency of human resources and labor abundant; (iii) Bali has social capital in the form of experience of farmer in farming and system social of Bali people easy to make group as diffusion media for innovation and technology, and (iv) Indonesia generally and Bali specially have four excess of nature which not have by most developed nations that is, length and intensity of irradiation, favourable temperature, free typhoon, and rainfall which enough. To developt the small businessman horticulture, so strategy able to do better through three step those are: (i) redistribution of main production asset like the agriculture land, can in the form of transfer of ownership or in the form of institutional arrangement which give opportunity to land poor farmer; (ii) increase the agriculture land productivity, pass change of technology and innovation, policy of economics and improve of institutional system, and (iii) investment in human resources through training and education purpose increase the knowledge and skill of horticulture farmer and agriculture government officer. To reach the high competitiveness of Bali horticulture products specially and Indonesia generally is by applying concept of agribusiness system, that is integrating subsystem of production with upstream and downstream agriculture industry, subsystem of marketing or commerce and subsystem of supporting institution. Beside that, removing constraints of substance and organization faced by small farmer and also increasing role of government and other relevant institution in facility and to control (not to regulate) development of horticulture business. To reach success development of horticulture business in Bali specially and in Indonesia generally, please learn from successful story of Thailand agribusiness development. Successfulness of products exporting of Thailand agribusiness horticulture is result of year’s hard work which involves much side, from king/queen until worker agribusiness, from lecturer/researcher until public society, and from government/financial institution until entrepreneur. Successful story of Thailand expected can become inspiration, lesson and consideration for Indonesia in the plan and execution of horticulture agribusiness development which orientation for global market, which is finally will positive affect toward increasing the prosperity of society in general and small businessman of horticulture specially.
Keywords: Development, Strategy, Small Farmer, Horticulture